Investment Decisions' Impact on Corporate Value: Analyzing Profitability, Leverage, Company Size, and Age Moderation Effects - Faridatul Munawaroh; Agus Munandar (International Journal of Social Science and Business, 2024)
The global economic issues affecting Indonesia's property and real estate sector highlight how investors evaluate company performance based on various factors such as cash availability, sales levels, debt, and company size. This study aims to analyze the impact of investment decisions on company value, moderated by profitability, with leverage, company size, and company age as control variables. This quantitative research use purposive selection approaches to selectively target property and real estate businesses that match particular criteria and were listed on the Indonesia Stock Exchange between 2018 and 2022. In order to validate the statistical model, the data analysis technique used is multiple linear regression, which aims to examine the correlations between numerous independent and dependent variables via the use of traditional assumption tests and hypothesis testing. According to this research, investment choices have a detrimental effect on a company's value; however, these effects may be mitigated by profitability. Control factors such as leverage, age, and size have a beneficial impact on the value of the firm. when combined with investment decisions moderated by profitability. These results underscore the importance of considering factors such as profitability, leverage, company size, and company age in investment decision-making to enhance company value.